Use of Multimedia Presentations in Chemistry Lessons for Non-Core Chemistry - Kholmirzayev Rapigjon Rasuljon ogli (Zien Journals, 2022)
Chemistry lessons are illustrated and illustrated using computer technology, multimedia elements, and pedagogical teaching methods. At the same time, it is said that such activities help students develop their intellectual abilities.
Keywords: computer technology; multimedia; problem-based learning technology; metals